Outcome of External Dacryocysto-Rhinostomy (DCR) Operation Without Silicone Tube Intubation (Anwer Khan Modern Medical College Journal, 2018)
Background: Dacryocysto-rhinostomy (DCR) is a bypass surgery in which an anastomosis is made between the medial wall of the lacrimal sac & the lateral wall of the nasal mucosa by cutting the intervening bone at the level of middle meatus to restore the flow of tears when the obstruction is beyond the common canaliculus. The aim of this study was to evaluate the surgical intervention of conventional external DCR without silicon tube intubation.Methods: This study was conducted at Jahurul Islam Medical College Hospital, Kishoregonj, from July 2016 to January 2018. Fifty cases with chronic dacryocystitis were selected for the study. The operation was done under local anaesthesia. The patients were followed up for 3 months.Result: The mean age of the patient at the time of surgery was 40.9±13.1 years ranged from 16 to 65 years. Male to female ratio was 1:2.1. There were three patients with reactionary haemorrhage, one wound infection, two with wound gap, one epicanthal fold and one granuloma formation. There were no failed DCR in this series.Conclusion: Conventional DCR is the most common oculoplastic surgery performed for managing epiphora due to nasolacrimal duct obstruction.Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 121-123